Separatrices: The crux of reconnection. (January 2015) - Lapenta, Giovanni; Markidis, Stefano; Divin, Andrey; Newman, David; Goldman, Martin
<x content-type="archive" xml:space="preserve">Abstract</x> Magnetic reconnection is one of the key processes in astrophysical and laboratory plasmas: it is the opposite of a dynamo. Looking at energy, a dynamo transforms kinetic energy in magnetic energy while reconnection takes magnetic energy and returns it to its kinetic form. Most plasma processes at their core involve first storing magnetic energy accumulated over time and then releasing it suddenly. We focus here on this release. A key concept in analysing reconnection is that of the separatrix, a surface (line in 2D) that separates the fresh unperturbed plasma embedded in magnetic field lines not yet reconnected with the hotter exhaust embedded in reconnected field lines. In kinetic physics, the separatrices become a layer where many key processes develop. We present here new results relative to the processes at the separatrices that regulate the plasma flow, the energization of the species, the electromagnetic fields and the instabilities developing at the separatrices.